Growth and stabilization of two-dimensional multiferroics MnI2. (15th May 2019) - Zhuo, La; Li, Yongkai; Wang, Xiangzhuo; Lu, Jiaze; Qiao, Lu; Chen, Dongyun; Zheng, Jingchuan; Xiong, Xiaolu; Peng, Xianglin; Li, Ji; Wang, Qinsheng; Duan, Junxi; et al.
Abstract: MnI2 is one of the important multiferroics materials with a layered, nearly two-dimensional (2D) structure due to van der Waals bonds. In this work, we developed physical vapor deposition and mechanical exfoliation methods to prepare 2D MnI2 flakes on amorphous SiO2 substrates. The morphologies, composition and structure properties of the 2D MnI2 flakes were characterized by optical microscopy, atomic force microscopy, scanning electronic microscope and Raman spectroscopy. Furthermore, we systematically studied the degradation of the MnI2 flakes. With h-BN and PMMA as protective materials, we improved the stability of the MnI2 flakes and slow down the degradation process under moisture conditions. In this regard, we provided MnI2 flakes as new 2D materials with effective protection, which may pave the way for the application of low dimensional multiferroics materials in the future.